Manajemen Usahatani Semangka di Desa Kubang Jaya Kecamatan Siak Hulu Kabupaten Kampar (Studi Kasus: Kelompok Usahatani Semangka Pak Andre) - Hidayah, Nurul; Edwina, Susy; Maharani, Evy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The implementation of farm management in Mr. Andre's watermelon farming group in Kubang Jaya Village has not been carried out optimally. The problem faced is that the supervisory function has not been carried out properly. This can have an impact on farmers' production results. This research aims to: 1) Know the application of watermelon farm management functions, 2) Analyze the income of farmers who apply watermelon farm management. The sampling technique was carried out on watermelon farmers in Mr. Andre's watermelon field in Kubang Jaya Village, Siak Hulu District, Kampar Regency who used the farm management function in their watermelon cultivation. The sample determination was carried out using the Census (Saturated Sampling), with the consideration that this research was a case study on Mr. Andre's watermelon field. The results showed that in the watermelon farming sapta carried out by watermelon farmers on Mr. Andre's land there were still problems covering several aspects such as land preparation, seeding and maintenance activities, while in the application of watermelon farm management functions there were obstacles in harvesting activities, namely the low level of supervision or controlling farming. The average revenue obtained by farmers is IDR 228,000,000/Lg/MT or IDR 38,000,000/ha/MT. Watermelon farm income received by farmers amounted to Rp69,171,056/Lg/MT or Rp11,528,509/ha/MT. The unit Break Even Point (BEP) for Mr. Andre's farming group in Kubang Jaya Village was obtained at 25,931 kg, with a price BEP of Rp2,090. The efficiency of watermelon farming resulted in a value of 5.72, indicating that each unit of input used in watermelon farming provides a profit so that it is feasible to cultivate.